Addressing gendered varietal and trait preferences in West African maize. (December 2020) - Tegbaru, Amare; Menkir, Abebe; Nasser Baco, Mohamed; Idrisou, Latifou; Sissoko, Dioukou; Eyitayo, Ayinde O.; Abate, Tsedeke; Tahirou, Abdoulaye
Highlights: No evidence to determine whether maize breeding programs has been favouring or disfavouring men or women farmers. No clear distinction between most of the drought tolerant maize varieties and hybrids preferred by men and women farmers. The inherent properties of the hybrids and open-pollinated maize varieties were the drivers of preferences of men or women farmers. Better breeding strategies that permit the development of gender-response products with greater potential impact on livelihoods. Need for better breeding strategies that permit the development of gender-response products with greater potential impact on improved food and nutritional security. Market opportunities exist for private seed companies to ensure th constant supply of seed for women and men user groups and sustain the seed value chain. Abstract: Maize is the most important cereal in Sub Saharan Africa; however, yields are significantly lower than those possible with improvements in cultivars and management. Maize breeding programs need to produce material with improved resistance to increasing environmental stresses and incorporate the man and women farmer preferred traits that relate to yield, postharvest, nutritional, and processing qualities. This research uses gender-disaggregated data recorded during participatory on-farm maize trials by the Stress Tolerant Maize Program conducted in agroecological zones of Benin, Nigeria and Mali) to identify men and women farmer's expressed varietal and trait preferences in order to evaluate plant breeding strategy. A multi-stage varietal and trait identification process was used to identify gender shared and distinctive varietal trait preferences for product development and dissemination. The data indicates that progress has been made by the Project in considering the range of traits valued by both men and women farmers and indicates those that should be considered for gender-focused product pipeline development in the future. The study concludes by underlining the need for adjustment in breeding to improve partnerships with food scientists, postharvest specialists and private seed sector on the packaging and delivery of technologies to farmers and other value chain actors.